Association between the Achievement of Target Range CKD-MBD Markers and Mortality in Prevalent Hemodialysis Patients in Taiwan by Using the Kidney Disease: Improving Global Outcomes Clinical Guidelines. (27th November 2016) - Liu, Ying; Lee, Wen-Chin; Cheng, Ben-Chung; Li, Lung-Chih; Lee, Chih-Hsiung; Chang, Wen-Xiu; Chen, Jin-Bor
Abstract : Background. This study evaluated the association between achieving target chronic kidney disease-mineral and bone disorder (CKD-MBD) marker levels and mortality in Taiwanese hemodialysis (HD) patients. Target levels were based on the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines. Methods. We performed a retrospective medical record review of 1126 HD patients between 2009 and 2013. A logistic regression model was used to evaluate the relationship between achieving target marker levels and the risk for all-cause and cardiovascular (CV) mortality. Reference target ranges were 7.9 ≤ calcium (Ca) ≤ 9.9 mg/dL, 2.4 ≤ phosphate (P) ≤ 4.7 mg/dL, and 144 ≤ intact parathyroid hormone (iPTH) ≤ 648 pg/mL. Results. Achievement of target P levels was associated with a lower risk for all-cause mortality compared to achievement of either target Ca or iPTH levels. Achieving target P + iPTH levels (OR 1.32) was associated with a lower odds ratio for all-cause mortality compared to achieving target Ca + P (OR 1.66) and Ca + iPTH (OR 1.43) levels. Similar trends were observed for CV mortality risk. Conclusions. The present study demonstrated that achieving serum P levels within the KDIGO target range is the most important factor for lowering mortality in HD patients.